2020
DOI: 10.31744/einstein_journal/2020ao5263
|View full text |Cite
|
Sign up to set email alerts
|

Physiological profile of adult male long-distance trail runners: variations according to competitive level (national or regional)

Abstract: Objective: To assess the health profile of community-dwelling older adults, according to sex, assisted by the Elderly Caregiver Program of the City of São Paulo. Methods: Secondary data of 535 older adults, assisted by ten Elderly Caregiver Program teams from the southern region of São Paulo, were collected from medical records and the Multidimensional Evaluation of Older People in Primary Care, after verifying the inclusion and exclusion criteria for the study and obtaining subjects' consent. Results: Older a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…Similarly, aerobic fitness per unit of body mass could be a factor in the endurance performance, which showed a correlation with the level of competition in ultra-long-distance runners [33]. The second ventilation threshold was also the best aerobic fitness variable [33]. These physiological variables, such as the second ventilation threshold, aerobic fitness per body unit, or muscle mass, could also be used for further studies to investigate the endurance performance of older athletes.…”
Section: Performance Gap Disappeared In Older Age Groupsmentioning
confidence: 97%
See 1 more Smart Citation
“…Similarly, aerobic fitness per unit of body mass could be a factor in the endurance performance, which showed a correlation with the level of competition in ultra-long-distance runners [33]. The second ventilation threshold was also the best aerobic fitness variable [33]. These physiological variables, such as the second ventilation threshold, aerobic fitness per body unit, or muscle mass, could also be used for further studies to investigate the endurance performance of older athletes.…”
Section: Performance Gap Disappeared In Older Age Groupsmentioning
confidence: 97%
“…Furthermore, it has been shown that lifelong endurance training can maintain muscle mass and function in the elderly [32]. Similarly, aerobic fitness per unit of body mass could be a factor in the endurance performance, which showed a correlation with the level of competition in ultra-long-distance runners [33]. The second ventilation threshold was also the best aerobic fitness variable [33].…”
Section: Performance Gap Disappeared In Older Age Groupsmentioning
confidence: 97%
“…Furthermore, it has been observed that lifelong endurance training can function and maintain muscle mass in the elderly [ 47 ]. Similarly, aerobic fitness per unit of body mass could be a factor in endurance performance, which showed a correlation with the level of competition in ultra–long-distance runners [ 48 ].…”
Section: Discussionmentioning
confidence: 99%